Comparison between sponsored and non-sponsored regarding personal administrative factors for SMEs from Kuwait during the COVID-19 pandemic - Alainati, Shaikhah (2024)
The purpose of this study is to examine the comparison between sponsored and non-sponsored personal administrative factors during the COVID-19 pandemic. Over the past decade, governments around the world have started to experiment with entrepreneurial ecosystems in an effort to drive enterprise development and innovation in their economies. However, there is no consensus for sustainable policy performance in ecosystem development. Drawing on literature from strategy, institutions, social behavior, and entrepreneurship, the purpose of this study is to examine the role of entrepreneurial personal skills, management business skills, and social sustainability in receiving government funding. Using a unique dataset of 948 entrepreneurs in Kuwait from 2020-2021, we analyze a sample of two groups: those who received funding and those who did not receive funding from the National Fund for Small and Medium Enterprise Development. The finding implies that individuals who did not obtain funds have higher performance indices in management and entrepreneurial business abilities but lower social sustainability. Furthermore, business owners who did not obtain financing are less likely to have closure plans. This research has significant practical implications for the way the government distributes funds to entrepreneurs. It suggests that the financing criteria may need to be reassessed, taking into account not only managerial and entrepreneurial talents but also social sustainability factors. The results can assist policymakers in understanding how efficiently and effectively resources are allocated, particularly in the context of assisting small and medium-sized businesses.